The Existence of Life and Death for Higher Education Applicants: Results of Qualitative Analysis - Melnyk , Volodymyr; Blikhar, Viacheslav; Kalka , Nataliya (Journal of Education Culture and Society, 2025)
Aim. The purpose of the study is to determine the peculiarities of the existence of life and death of persons of youthful age during the crisis period of society, namely during the military actions in Ukraine.Methods. The study was conducted by qualitative analysis of associative links to the word "life" and the word "death". The subjects had to find at least 5 association words for the word "life" and the word "death" and 1 image, picture or photo for the word "life" and the word "death". Results. The associative chain to the word "life" in the sample looks as follows: "joy" - "love" - "happiness" - "family" - "being" - " freedom"-"sun"-"health"-"peace". In the images associated with the word "life", the symbols of the sun, swing, balloons, butterfly, sea, man, nature, family, couple in love, friends, man, clock. The associative chain to the word "death" includes the following words: "end (finish)"-"pain"-"sadness"-"grief"-"war"-"fear"-"tears"-"darkness"-"tranquility"-"emptiness").Conclusions. On the basis of qualitative analysis, we believe that the existence of life of higher education applicants is based on positive emotional experiences and the presence of deep feelings, which is an indicator of satisfaction of life. The social sphere (family, friends) and the motivational sphere (success and achievement) are an important component of the existence of young people's lives. The existence of the death of young people is focused on negative emotional experiences (sadness, fear, despair, disappointment), which are related to the losses and the reality of the war in which they are.